Environmental Justice vs Global Capitalism: Experiences, Debates and Conﬂicts in Peru - Canaza Choque, Franklin Américo (2018)
The study stops its analysis in the multiple socio-environmental manifestations germinated in the Peruvian territory against a globalized capitalism. The methodology takes its momentum in the documentary research and the bibliographical analysis. Faced with the expansion of mining activity in recent years and the high socio-environmental impacts provoked in Peru, those affected undertake struggles in search of the recognition of environmental justice. For the vulnerable in Santa Ana (2011), Conga (2011-2014), Las Bambas (2015) and Tia Maria (2015) the idea of climate justice is a right that is being injured.